Produção, usos e apropriações de uma imagem: o processo de iconização da fotografia da mulher de turbante, de Alberto Henschel: Production, uses and appropriations of an image: the process of iconization of the photograph of the woman in a turban, by Alberto Henschel (Revista de História da UEG (REVHIST), 2020)
The article focuses on the portrait of a black woman wearing a turban, taken by Alberto Henschel, around 1870, in Rio de Janeiro. Among the many images of black “types” produced by the German photographer, this is certainly one of the best known and most appropriated in the last decade. The analysis of the production, circulation and consumption of this photograph aims to examine the relationship between its massive use and the invisibility or subordination imposed on black people, especially black women, by structural racism. We problematize, in particular, the anachronistic identification of the woman portrayed as Luísa Mahin, Luís Gama's mother, who would have been one of the leaders of the malês Revolt, in Bahia, in 1835. The production of meanings that this photograph engenders, the effects it produces in its uses and displacements, its potential for iconization, as well as its agency, are some questions that we seek to discuss, following Ana Mauad’s analyses about the need to take the image as an agent of history, not simply as a source of information about the past or the subject of a historical study.Keywords: Black woman. Alberto Henschel. Photography, XIX century. Visual Culture.